Multivariate analysis of periodontal disease and associated risk factors in a population of south Brazil - Eliane Gaio; Ademir Franco; Álex Moreira Herval; Renata Prata Cunha Bernardes Rodrigues; Ítalo de Macedo Bernardino; Luiz Renato Paranhos; Lilian Rigo (Acta Scientiarum. Health Sciences, 2019)
Periodontal disease is a multifactorial oral health problem that may be associated with several risk factors. This study aimed to investigate the prevalence rates of risk factors and socioeconomic aspects of patients with periodontal disease. One-hundred and twelve patients underwent the application of a socioeconomic questionnaire and intraoral examinations. The later was founded in the search and registration of gingival bleeding, dental calculus and periodontal pockets. In a multivariate analysis using the Chi-square Automatic Interaction Detection (CHAID), the clinical findings were tested for their association with socioeconomic information, such as patient’s level of education. Gingival bleeding, dental calculus and periodontal pockets were detected in 82.1, 88.4 and 38.4% of the sample, respectively. Patients with lower level of education presented higher rates of gingival bleeding (p = 0.018), calculus (p = 0.001) and periodontal pockets (p = 0.001). Other socioeconomic factors, such as age, knowledge of oral hygiene tools, and access to dental services also showed statistically significant associations with periodontal diseases (p < 0.05). These outcomes corroborate with most of the previous scientific literature. In practice, they may contribute to the development of oral health care strategies to reach more effectively populations in need for optimal dental services.